Pengembangan Metode Pembelajaran Interaktif dalam Kurikulum PAI - Trimahmudi, Trimahmudi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of preparing this work is to analyze learning evaluation innovations in the PAI curriculum. Literature review method to examine learning evaluation innovations in the PAI curriculum, by collecting and analyzing data from scientific journals, books, research reports and related policy documents. Data was collected through literature searches in academic databases, then selected and analyzed based on categories such as types and methods of evaluation, as well as their impact on PAI learning. Analysis results are synthesized to understand common patterns, key findings and gaps, and interpreted to provide practical recommendations that are reported comprehensively. The result of this work is innovation in learning evaluation in the Islamic Religious Education (PAI) curriculum in Indonesia which faces challenges such as unclear policies and limited time allocation, so that it requires continuous evaluation to ensure educational goals are achieved. This innovation is important to overcome time constraints, lack of integration of religious values, and increase teacher competence. Appropriate evaluation can identify curriculum strengths and weaknesses and provide recommendations for improvement. PAI material in Madrasas covers various sub-themes with an assessment of students' attitudes, knowledge and skills expected from the Competency Performance Indicators (GPA). Improving the quality of teachers and collaboration between central and regional governments is very important for developing a more effective and relevant PAI curriculum.